Hybrid Renewable-Hydrogen and Natural Gas Methanol Synthesis: A Techno-Economic Analysis - Uthman, H.; Agboola, D. T.; Garba, M. U.; Azeez, O. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Conventional methanol production is highly carbon-intensive due to its reliance on fossil-derived hydrogen from reforming processes. The purpose of this study is to assess the viability of incorporating renewable hydrogen from solar-powered electrolyzers to reduce the environmental impact of natural gas-based methanol production and replace the requirement for reformer hydrogen. Aspen HYSYS 14.0 was used to model and compare two hybrid configurations: Steam Methane Reformer–Autothermal Reformer (SMR–ATR) with electrolyzer and Autothermal Reformer–Heat Transfer Exchange Reformer (ATR-HTER) with electrolyzer, with their conventional counterparts in a steady-state techno-economic and environmental assessment. All process configurations' technical viability was confirmed by mass and energy balance analyses. The findings showed that the configurations differ significantly in terms of production costs, methanol purity, and utility demand. Although it produced methanol with a purity of only 50.43%, requiring downstream upgrading, the SMR–ATR with electrolyzer design achieved the lowest levelized cost of methanol (LCOM) at USD 95.29 per tonne and the lowest utility requirement (468,113 kWh). The ATR–HTER with electrolyzer design, on the other hand, needed a significantly higher electricity consumption of about 11.76 million kWh, raising the LCOM to USD 119.12 per tonne despite achieving high methanol purity (98.56%) and efficient renewable hydrogen integration. These results suggest that excessive energy usage might negatively impact economic performance, even if electrolyzer integration can improve carbon efficiency and lessen reliance on fossil-based hydrogen when powered by low carbon electricity. Overall, electrolyzer-assisted methanol production is most economical in regions with plentiful natural gas and access to low-cost renewable electricity, such as Nigeria, which helps to advance United Nations Sustainable Development Goals 7, 9, and 13.